Peran Wukuf Arofah Terhadap Praktek Ekonomi - Muslimin (el Hakim Press, 2022)
The purpose of this study was to determine the perception of entrepreneurs when the congregation towards the economy was in the area of ​​their Arofah wukuf arofah ritual. The existence of the Arofah field should be a solution to the accommodation needs needed by pilgrims worldwide, from sector entrepreneurs who are provided to support the smooth wukuf in Arofah because the purpose of wukuf is to realize the worship of khusu 'tadarru, taqarrub to Allah SWT. The method used in this research is qualitative which is supported by primary data. The research sample in this study was only a few organizers, one of which was PT Musafir Internasional. The results of this study are that there are approximately 200 congregations. The reasons for leaving this year include that the age of the congregation is limited to less than 65 years, they use this bureau to guarantee the fast issuance of the MoFA visa, the perpetrators of course have difficulty finding the exact date of departure because of the busy conditions of the congregation. And finance wukuf arofah is an embryo of economic strength in this country, in a season it is able to finance life in the next year, in this era it is able to become a system that can prosper the family. In times of crisis, he was able to escape bankruptcy, even though he did not receive any help from anywhere because the pilgrims had paid up front before attending Arofah. The concept that contains Arofah's accommodation has become a force in reviving the country's economy. The financial system, which is revolving around every year, is growing rapidly and plays an important role in allocating resources and promoting economic development.